Intangible Cultural Heritage Based on AR Technology - Tong, Chaoran; Hee-Gyun, Kim (Bright Publisher, 2022)
With the development of society and the improvement of people's material living standards, Internet technology has penetrated into all aspects of people's lives, and AR technology has gradually entered people's lives. At the same time, all sectors of society are paying more and more attention to the development and protection of ICH and other traditional cultures. Although many experts and scholars have conducted research and discussion in this area before and after, due to the late start time, shortage of technology and incomplete technical personnel and other issues, no good solution has been found, and little gain has been achieved. Based on this, this article adopts a new perspective, using the advantages of the modern big data society, through the current advanced AR technology and digital management, aiming to find the best plan for the development and protection of ICH, with a view to the domestic ICH Provide reference and reference for development and protection. This article uses data analysis, comparison and experiment methods. It first introduces the theoretical aspects of ICH and proposes specific measures for its digital development and protection, and then quotes the traditional cultural heritage of shadow play as as a specific example, 60 audiences were randomly surveyed by questionnaire survey, and divided into 3 groups according to age, and they were subjected to issues such as viewing attitude and effect of traditional shadow play based on AR technology and traditional shadow play according to the investigation, it is concluded that the traditional shadow play based on AR technology is more popular with the audience, and compared with the traditional shadow play, the viewing effect is better.